The influence of spelling on the production and storage of words with allophonic variants of /h/ in Korean. (21st July 2015) - HAN, JEONG-IM; CHOI, TAE-HWAN
ABSTRACT: This study examined the role of orthography in the production and storage of spoken words. Korean speakers learned novel Korean words with potential variants of /h/, including [ɦ] and ø. They were provided with the same auditory stimuli but with varying exposure to spelling. One group was presented with the letter for ø (<ㅇ>), the second group, the letter for [ɦ] (<ㅎ>), and the third group, auditory input only. In picture-naming tasks, the participants presented with <ㅇ> produced fewer words with [ɦ] than those presented with <ㅎ>. In a spelling recall task, the participants who were not exposed to spelling displayed various types of spellings for variants, but after exposure to spelling, they began to produce spellings as provided in the task. These results suggest that orthographic information influences the production of words via an offline restructuring of the phonological representation.